GREEN ACCOUNTING: GREENHOUSE EFFECT REDUCTION AND SUSTAINABLE ECONOMIC GROWTH - Riza Praditha; Robert Jao; Supandi Supandi; Amelia Alifyanda Putri (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2026)
The implementation of Green Accounting is a strategic step in aligning the ambition of sustainable economic growth with concrete efforts to reduce the greenhouse effect to maintain the stability of the global ecosystem. This research examined the factors influencing MSMEs' decisions to implement green accounting using an isomorphism approach, and examine its role in reducing the greenhouse effect and sustainable economic growth. This study used a 2x3 full factorial within-subjects field experimental design. The experimental subjects were MSMEs and were divided into two groups. Each group received the same experimental treatment with three categories of isomorphism: normative, coercive, and mimetic. This research shows that the perceptions and behavior of MSME entrepreneurs can be influenced by external organizational pressure. Using the isomorphism approach, it can be explained that entrepreneurs will implement corporate social responsibility if there is pressure from government regulations (coercive), pressure from other entrepreneurs considered role models (mimetic), and pressure from their knowledge capabilities and ability to form organizational commitment (normative). These results have significant implications for government policy, suggesting that the implementation of green economy business concepts should be supported by education and by promoting business success to foster greater environmental awareness among business actors.